The Influence of Organizational Culture and Interpersonal Communication on Employee Performance - Oktavianto, Ananda Riski; Irawanto, Dodi Wirawan (Jurnal Kewirausahaan dan Inovasi, 2024)
This study aims to explore how organizational culture and interpersonal communication impact employee performance, focusing on the XYZ company in the oil and gas industry. The research adopts an associative approach using quantitative methods. A sample of 66 respondents was conveniently selected from a population of 152 within the company. The participants, current employees of XYZ company, responded to a Likert scale questionnaire ranging from 1 to 5. Statistical Package for the Social Sciences (SPSS) was used for validity, reliability, and classical assumption tests. Multiple linear regression tests were applied for data analysis, and hypothesis testing was conducted for both partial and simultaneous assessments. Results reveal that organizational culture (X1) has a positive partial and simultaneous influence on employee performance (Y). However, interpersonal communication (X2) does not exhibit a partial or simultaneous impact on employee performance (Y). Notably, both organizational culture (X1) and interpersonal communication (X2) variables positively influence employee performance (Y) when considered both partially and simultaneously.   Abstrak Penelitian ini bertujuan mengeksplorasi dampak budaya organisasi dan komunikasi interpersonal terhadap kinerja karyawan, difokuskan pada perusahaan XYZ di sektor minyak dan gas. Jenis penelitian ini adalah asosiatif dengan pendekatan kuantitatif. Sampel terdiri dari 66 responden yang dipilih secara convenience sampling dari populasi 152 di perusahaan tersebut. Responden adalah karyawan aktif di XYZ. Kuesioner menggunakan skala Likert dengan skor 1-5. Analisis data dilakukan menggunakan Statistical Package for the Social Sciences (SPSS) untuk uji validitas, reliabilitas, dan uji asumsi klasik. Uji regresi linier berganda digunakan untuk analisis data, dan uji hipotesis dilakukan baik secara parsial maupun simultan. Hasil menunjukkan budaya organisasi (X1) berpengaruh positif parsial dan simultan terhadap kinerja karyawan (Y). Sebaliknya, komunikasi interpersonal (X2) tidak berpengaruh parsial atau simultan terhadap kinerja karyawan (Y). Sementara itu, budaya organisasi (X1) dan komunikasi interpersonal (X2) berdampak positif baik secara parsial maupun simultan terhadap kinerja karyawan (Y).